THE EFFECT OF ORGANIZATIONAL STRUCTURE, LEADERSHIP BEHAVIORS AND DECISION MAKING TOWARD ORGANIZATION COMMITMENT A CausaL Study on Association of Indonesian Islamic Education Teachers (AGPAII) Bekasi City - MADALI, MADALI (Jurnal Ilmiah Educational Management, 2016)
The object of this study was to determine the effect of organizational structure, leadership behaviors, and decision making towards organizational commitment DPD board AGPAII Bekasi City. This study uses a quantitative approach with survey method and path analysis techniques. The study population was all members of DPD AGPAII Bekasi city. This study sampled 55 administrators. This research data collection techniques using a questionnaire with five alternative answers (1) always (2) often (3) sometimes, (4) rarely, (5) never. At each study variable. Development of instruments for each variable through the conceptual definition, operational definition, grating instrument, testing the validity and reliability calculation. Data analysis techniques with descriptive statistics, inferential. The findings lead to recommendations for improvement of organizational structure will lead to increased organizational commitment, improved behavior of a leader with some of the leadership style will enhance organizational commitment, decision-making right individuals will increase organizational commitment, improvement of the organizational structure will improve decision making, improvement leader behavior will lead to increased retrieval decision